ANALISIS KREDIT BERMASALAH USAHA DAN NON USAHA MIKRO KECIL MENENGAH PADA PERBANKAN INDONESIA - Nurul Khotimah (Jurnal Ilmiah Ekonomi Bisnis, 2015)
MSMEs (Micro, Small and Medium Enterprises) recently had a very important contribution in the Indonesian economy , in addition to the SME sector most vulnerable rising NPLs. The purpose of this study was to analyze the level of non-performing loan ratio of each - each section of Micro, Small and Medium Enterprises in the sector of SMEs and MSM. Data used is secondary data sourced from the BI report in 2013, the data of Credit and Credit NPL SMEs by Group Bank, Bank Limited, Bank of local government and the National Private Bank in April 2012 to March 2013. Data were processed and analyzed with the help of application SPSS. The analysis tool used is the descriptive statistics, analysis of variance ANOVA different test, the method of LSD (Least Significance Differences). The results showed the development of the NPL ratio period April 2012 - March 2013 at the highest MSME sector on loans disbursed by the Bank of Local Government, then the lowest NPL Owned Banks and Private Banks masional. MSM Sector highest NPL ratio for loans disbursed by the Bank Limited, National Private Bank and Bank lowest NPL on local government.  Keywords: credit risk, foreign exchange banks, non-bank foreign exchange, Micro, Small and Medium Enterprises, GDP